P30-66 EPAA review of regulatory requirements for a second (non-rodent) species in repeated-dose toxicity studies and potential 3Rs opportunities - N. Printemps; M. Aggarwal; M. Anderton; P. Bishop; F. Chanut; K. Clark; M. Corvaro; P. Deford; O. Doehr; J. Fretton; J.-C. Garcin; A. Kampkoetter; et al. (Toxicology Letters, 2025)

Investigating overpressure BLEVE effects on 100 % liquid full vessel - E.M. Laamarti; A.M. Birk; C. Chanut; F. Heymes (Process Safety and Environmental Protection, 2025)

River Drying Causes Local Losses and Regional Gains in Aquatic Invertebrate Metacommunity Diversity: A Cross‐Continental Comparison - Daniel Escobar‐Camacho; Julie Crabot; Rachel Stubbington; Judy England; Romain Sarremejane; Núria Bonada; José María Fernández‐Calero; Miguel Cañedo‐Argüelles; Carla Ferreira Rezende; Pierre Chanut; Zoltán Csabai; Andrea C. Encalada; et al. (Global Change Biology, 2025)
Drying river networks include non‐perennial reaches that cease to flow or dry, and drying is becoming more prevalent with ongoing climate change. Biodiversity responses to drying have been explored mostly at local scales in a few regions, such as Europe and North America, limiting our ability to predict future global scenarios of freshwater biodiversity. Locally, drying acts as a strong environmental filter that selects for species with adaptations promoting resistance or resilience to desiccation, thus reducing aquatic α‐diversity. At the river network scale, drying generates complex mosaics of dry and wet habitats, shaping metacommunities driven by both environmental and dispersal processes. By repeatedly resetting community succession, drying can enhance β‐diversity in space and time. To investigate the transferability of these concepts across continents, we compiled and analyzed a unique dataset of 43 aquatic invertebrate metacommunities from drying river networks in Europe and South America. In Europe, α‐diversity was consistently lower in non‐perennial than perennial reaches, whereas this pattern was not evident in South America. Concomitantly, β‐diversity was higher in non‐perennial reaches than in perennial ones in Europe but not in South America. In general, β‐diversity was predominantly driven by turnover rather than nestedness. Dispersal was the main driver of metacommunity dynamics, challenging prevailing views in river science that environmental filtering is the primary process shaping aquatic metacommunities. Lastly, α‐diversity decreased as drying duration increased, but this was not consistent across Europe. Overall, drying had continent‐specific effects, suggesting limited transferability of knowledge accumulated from North America and Europe to other biogeographic regions. As climate change intensifies, river drying is increasing, and our results underscore the importance of studying its effects across different regions. The importance of dispersal also suggests that management efforts should seek to enhance connectivity between reaches to effectively monitor, restore and conserve freshwater biodiversity.

Correlations to estimate the ground loading from small scale propane BLEVE experiments - E.M. Laamarti; A.M. Birk; C. Chanut; F. Heymes (Process Safety and Environmental Protection, 2024)

Convergence in floodplain pond communities indicates different pathways to community assembly - P. C. M. Chanut; F. J. Burdon; T. Datry; C. T. Robinson (Aquatic Sciences, 2023)
Disturbance can strongly influence ecosystems, yet much remains unknown about the relative importance of key processes (selection, drift, and dispersal) in the recovery of ecological communities following disturbance. We combined field surveys with a field experiment to elucidate mechanisms governing the recovery of aquatic macroinvertebrates in habitats of an alluvial floodplain following flood disturbance. We monitored macroinvertebrates in 24 natural parafluvial habitats over 60 days after a major flood, as well as the colonization of 24 newly-built ponds by macroinvertebrates over 45 days in the same floodplain. We examined the sources of environmental variation and their relative effects on aquatic assemblages using a combination of null models and Mantel tests. We also used a joint species distribution model to investigate the importance of primary metacommunity structuring processes during recovery: selection, dispersal, and drift. Contrary to expectations, we found that beta diversity actually decreased among natural habitats over time after the flood or the creation of the ponds, instead of increasing. This result was despite environmental predictors showing contrasting patterns for explaining community variation over time in the natural habitats compared with the experimental ponds. Flood heterogeneity across the floodplain and spatial scale differences between the experimental ponds and the natural habitats seemingly constrained the balance between deterministic and stochastic processes driving the ecological convergence of assemblages over time. While environmental selection was the dominant structuring process in both groups, biotic interactions also had a prominent influence on community assembly. These findings have profound implications towards understanding metacommunity structuring in riverscapes that includes common linkages between disturbance heterogeneity, spatial scale properties, and community composition.

Evaluation of Structured and Unstructured Models for Application in Operational Ocean Forecasting in Nearshore Waters - Shannon Nudds; Youyu Lu; Simon Higginson; Susan P. Haigh; Jean-Philippe Paquin; Mitchell O’Flaherty-Sproul; Stephanne Taylor; Hauke Blanken; Guillaume Marcotte; Gregory C. Smith; Natacha B. Bernier; Phillip MacAulay; et al. (Journal of Marine Science and Engineering, 2020)
The oceanography sub-initiative of Canada’s Oceans Protection Plan was tasked to develop high-resolution nearshore ocean models for enhanced marine safety and emergency response, fitting into the multi-scale, multi-level nested operational ocean forecasting systems. For decision making on eventual 24/7 operational support, two ocean models (a structured grid model, NEMO (Nucleus for European Modelling of the Ocean); and an unstructured grid model, FVCOM (Finite Volume Coastal Ocean Model), were evaluated. The evaluation process includes the selection of the study area, the requirements for model setup, and the evaluation metrics. The chosen study area, Saint John Harbour in the Bay of Fundy, features strong tides, significant river runoff and a narrow tidal-river channel. Both models were configured with the same sources of bathymetry and forcing data. FVCOM achieved 50-100 m horizontal resolution in the inner harbour and included wetting/drying. NEMO achieved 100 m resolution in the harbour with a three-level one-way nesting configuration. Statistical metrics showed that one-year simulations with both models achieved comparable accuracies against the observed tidal and non-tidal water levels and currents, temperature and salinity, and the trajectories of surface drifters, but the computational cost of FVCOM was significantly less than that of NEMO.

High-resolution modelling of a coastal harbour in the presence of strong tides and significant river runoff - Jean-Philippe Paquin; Youyu Lu; Stephanne Taylor; Hauke Blanken; Guillaume Marcotte; Xianmin Hu; Li Zhai; Simon Higginson; Shannon Nudds; Jérôme Chanut; Gregory C. Smith; Natacha Bernier; et al. (Ocean Dynamics, 2020)
In the context of Canada’s Ocean Protection Plan (OPP), improved coastal and near-shore modelling is needed to enhance marine safety and emergency response capacity in the aquatic environment. In this study, the Nucleus for European Modelling of the Ocean (NEMO) is adopted to develop an ocean forecasting system for Saint John harbour in the Bay of Fundy, on the east coast of Canada. The challenging regional oceanography is characterized by the presence of some of the world’s strongest tides, significant river runoff and complicated geometry. A three-level one-way nesting approach is used to downscale from a 1/12° North Atlantic-Arctic regional model to very-high-resolution port-scale around Saint John harbour. The three nested grids cover the outer shelf, the Bay of Fundy and finally the approach to the harbour with resolutions of 2.5 km, 500 m and 100 m respectively. Due to the lack of accurate runoff data at the Saint John River outlet, the model’s lateral open boundary condition is modified to introduce the river forcing with the observed time series of water level near the mouth of the river. Evaluation with observational data demonstrates the model’s accuracy for the simulation of tidal elevation and currents, non-tidal water level and currents, temperature and salinity. Comparison with the observed sea surface temperature demonstrates the improved model accuracy through increasing the horizontal resolution. Virtual Lagrangian trajectories computed using the modelled surface currents and including wind effects show good agreement with the observed trajectories of different types of surface drifters. This study demonstrates the capability of the NEMO modelling framework to provide very-high-resolution modelling at port-scale resolution for the Saint John harbour.

High-resolution modeling of the mean flow and meso-scale eddy variability around the Grand Banks of Newfoundland - Li Zhai; Youyu Lu; Simon Higginson; Fraser Davidson; Frédéric Dupont; François Roy; Jérôme Chanut; Gregory C. Smith (Ocean Dynamics, 2015)

Corrigendum to "NEMO on the shelf: assessment of the Iberia–Biscay–Ireland configuration" published in Ocean Sci., 9, 745–771, 2013 - C. Maraldi; J. Chanut; B. Levier; N. Ayoub; P. De Mey; G. Reffray; F. Lyard; S. Cailleau; M. Drévillon; E. A. Fanjul; M. G. Sotillo; P. Marsaleix (Ocean Science, 2013)

NEMO on the shelf: assessment of the Iberia–Biscay–Ireland configuration - C. Maraldi; J. Chanut; B. Levier; N. Ayoub; P. De Mey; G. Reffray; F. Lyard; S. Cailleau; M. Drévillon; E. A. Fanjul; M. G. Sotillo; P. Marsaleix (Ocean Science, 2013)
This work describes the design and validation of a high-resolution (1/36°) ocean forecasting model over the "Iberian–Biscay–Irish" (IBI) area. The system has been set-up using the NEMO model (Nucleus for European Modelling of the Ocean). New developments have been incorporated in NEMO to make it suitable to open- as well as coastal-ocean modelling. In this paper, we pursue three main objectives: (1) to give an overview of the model configuration used for the simulations; (2) to give a broad-brush account of one particular aspect of this work, namely consistency verification; this type of validation is conducted upstream of the implementation of the system before it is used for production and routinely validated; it is meant to guide model development in identifying gross deficiencies in the modelling of several key physical processes; and (3) to show that such a regional modelling system has potential as a complement to patchy observations (an integrated approach) to give information on non-observed physical quantities and to provide links between observations by identifying broader-scale patterns and processes. We concentrate on the year 2008. We first provide domain-wide consistency verification results in terms of barotropic tides, transports, sea surface temperature and stratification. We then focus on two dynamical subregions: the Celtic shelves and the Bay of Biscay slope and deep regions. The model–data consistency is checked for variables and processes such as tidal currents, tidal fronts, internal tides and residual elevation. We also examine the representation in the model of a seasonal pattern of the Bay of Biscay circulation: the warm extension of the Iberian Poleward Current along the northern Spanish coast (Navidad event) in the winter of 2007–2008.

Towards a regional ocean forecasting system for the IBI (Iberia-Biscay-Ireland area): developments and improvements within the ECOOP project framework - S. Cailleau; J. Chanut; J.-M. Lellouche; B. Levier; C. Maraldi; G. Reffray; M. G. Sotillo (Ocean Science, 2012)
The regional ocean operational system remains a key element in downscaling from large scale (global or basin scale) systems to coastal ones. It enables the transition between systems in which the resolution and the resolved physics are quite different. Indeed, coastal applications need a system to predict local high frequency events (inferior to the day) such as storm surges, while deep sea applications need a system to predict large scale lower frequency ocean features. In the framework of the ECOOP project, a regional system for the Iberia-Biscay-Ireland area has been upgraded from an existing V0 version to a V2. This paper focuses on the improvements from the V1 system, for which the physics are close to a large scale basin system, to the V2 for which the physics are more adapted to shelf and coastal issues. Strong developments such as higher regional physics resolution in the NEMO Ocean General Circulation Model for tides, non linear free surface and adapted vertical mixing schemes among others have been implemented in the V2 version. Thus, regional thermal fronts due to tidal mixing now appear in the latest version solution and are quite well positioned. Moreover, simulation of the stratification in shelf areas is also improved in the V2.